Variación del color del cuerpo del camarón Cryphiops caementarius durante el ciclo de muda - Terrones España, Shirley (2022)
The aim of the study was to evaluate the variation in body color of Cryphiops caementarius prawn during the molting cycle. Eighty-seven adult prawn (50 males and 37 females) of 5.25 to 8.52 cm total length from the Pativilca River (Peru) were used. The stage of the molting cycle was determined by microscopic examination of the inner edge of the exopodite of the uropods. The color of the prawn body was evaluated in the raw stage and after cooking in water at 100 ºC for 2 min, and in each case, it was photographed with a digital camera. The analysis of the digital images was performed in the dorsal and central area of the second abdominal segment and in the dorsal and central area of the posterior end of the cephalothorax. The RGB color mode of the Adobe Photoshop CS6 program was used for digital evaluation of body color. The body color of raw male prawn is yellowish or light brown in the postmoult and dark brown in the intermoult and premoult; and after cooking, it is orange in the postmoult and reddish in the intermoult and premoult. The body color of the female prawn does not vary during the molting cycle; in raw prawn the color tone is light brown in the postmoult and in some stages of the premoult; on the other hand, after cooking the color tone is orange in all stages of the molting cycle. The dark shade of the body color of only the raw male prawn produced the most intense reddish coloration after cooking. The body color of the raw and cooked male prawn varied with the molting cycle; in contrast, in the female, both raw and cooked, it was similar during the molting cycle.